Radium isotope fingerprinting of permafrost ‐ applications to thawing and intra‐permafrost processes. (25th April 2019) - Weinstein, Yishai; Rotem, Dotan; Kooi, Henk; Yechieli, Yoseph; Sültenfuß, Jurgen; Kiro, Yael; Harlavan, Yehudit; Feldman, Mor; Christiansen, Hanne H.
Abstract: Permafrost in circum‐polar regions has been recently undergoing thawing, with severe environmental consequences, including the release of greenhouse gases and amplification of global warming. Although highly important, direct methods of tracking thawing hardly exist. In a research study conducted at Adventdalen, Svalbard, we identified a permafrost radioisotope fingerprint, and show that it can be used to track thawing. Ratios of long‐ to the shorter‐lived radium isotopes are higher in ground ice than in active layer water, which we attribute to the permafrost closed system and possibly to the long residence time of ground ice in the permafrost. Also, daughter–parent 224 Ra/ 228 Ra ratios are lower in permafrost than in the active layer. These fingerprints were also identified in a local stream, confirming the applicability of this tool to tracing thawed permafrost in periglacial watersheds. A combination of radium isotope ratios and 3 H allowed the identification of recent intra‐permafrost segregation processes. The permafrost radium fingerprint should be applicable to other permafrost areas, which could assist in regional quantification of the extent of permafrost thawing and carbon emissions to the atmosphere.